Pola Komunikasi Warga NU Etnis Madura sebagai Budaya Aternalistik - Akhmad Haryono (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This article aims to discribe the communication patterning of WNUEM, that involves the community of NU and kiai as participant. The qualitative method and ethnography of communication approach is used to attain the goal of research. The research found, that the communication patterning of WNUEM reflect the paternalistic culture, that has became the tradition since their living in Islamic boarding house.